A practical approach to financial management - Dixon, R. (London : Financial training publications Limited, 1986)
The task of financial management is to facilitate the achievement of organization objectives by obtaining financial resources and then using them profitably and effectively.
Includes bibliographical references and index.
hza 29/08/2018
Loans
Keywords: Financial management